Quality of death in the river buffalo (Bubalus bubalis) - Mota-Rojas, Daniel (2021)
Results on appropriate, inappropriate, and painful slaughtering methods of river buffalo (Bubalus bubalis) are discussed. Undesirable consequences of poor desensitization and/or slaughtering procedures, causing pain and suffering to animals, are also approached.  These considerations are relevant as unsuitable methods can reduce consumer acceptance and commercial value of the meat obtained from animals undergoing deficient slaughtering procedures due to a lack of concern regarding their welfare. Relevant databases –Scopus, Science Direct, and PubMed– were searched for this review, including keywords such as pain, slaughter, stunning, Bubalus bubalis, and animal welfare. A detailed description of river buffalo's encephalic anatomy was compared to cattle concerning correct stunning and slaughter methods. The neurobiological processes of pain felt by animals when inadequately desensitized was also examined. Finally, recent findings on stunning methods for buffaloes were discussed, including encephalography. It was concluded that different animal species may require different stunning methods; at the same, time the optimal anatomical site also varies between species. Therefore, it is of the utmost importance to train the personnel performing these procedures (transport, stunning, slaughtering) to avoid mishandling that jeopardizes animal welfare by generating stimuli that trigger neurophysiological responses and, in turn, translate into pain during slaughter and reduced meat quality.